Telephone Survey Versus Panel Survey Samples Assessing Knowledge, Attitudes and Behavior Regarding Animal Welfare in the Red Meat Industry in Australia - Hemsworth, Lauren M.; Rice, Maxine; Hemsworth, Paul H.; Coleman, Grahame J. (Frontiers in Psychology, 2021)
Surveys are used extensively in social research and, despite a lack of conclusive evidence of their ‘representativeness’, probability internet panel surveys are being increasingly used to make inferences about knowledge, attitude and behaviour in the general population regarding a range of socially relevant issues. A large-scale survey of Australian public attitudes and behaviour towards the red meat industry was undertaken. Samples were obtained using a random digit dialling telephone survey (Computer-Assisted Telephone Interviewing-CATI, n=502 respondents) and a probability internet panel survey (PANEL, n=530 respondents) to examine differences between the two samples regarding attitudes and behaviour relating to livestock use and welfare. There was little difference in demographics between the CATI and the PANEL surveys apart from highest level of education, however there were differences between the two samples in both attitudes and behaviour toward the red meat industry after controlling for education levels. The PANEL respondents gave generally more conservative responses than did the CATI respondents in the sense that they were more positive towards the livestock industries and animal welfare within these industries. Differences were also found between the respondents of the two samples regarding behaviour that relates to the red meat industry, both community and consumer behaviour. PANEL respondents were less engaged in community behaviours performed in opposition of the red meat industry when compared with the CATI sample. The majority of CATI and PANEL respondents were red meat eaters and there was no difference between respondents of the two samples in relation to red meat consumption, however there were fewer vegetarians and vegans in the PANEL survey.. Possible reasons for the observed differences are discussed however, a definitive answer will depend on further research to identify the specific psychological factors that differ between samples derived from different survey methodologies.